A Literature Review of Community-Based Interventions for Stunting Reduction in Children under Five - Afaninda Dwi Khairini; Titih Huriah (Journal of Public Health Sciences, 2025)
Stunting is a significant chronic nutritional problem in Indonesia and the world, caused by long-term malnutrition, especially in the first 1000 days of life. Community-based interventions effectively reduce stunting rates by involving the community in health promotion, providing nutritious food, environmental sanitation, and education for pregnant and lactating mothers. This narrative literature review aims to assess the effectiveness of community-based interventions in reducing stunting among children under five years old. A structured literature search was conducted using three electronic databases: PubMed, ProQuest, and Emerald Insight. The search strategy applied Boolean operators and was framed as follows: community-based intervention AND stunted. Filters included publication years 2020–2025, articles available in full text, written in English or Indonesian, and focused on children under five. The initial search yielded 628 articles. After removing 15 duplicates and excluding irrelevant studies based on population, topic, or article type, 12 articles were selected for final analysis. The results show from 12 articles, there are six articles discussed about nutrition education, three articles about supplementary food and three articles about water and sanitation hygiene. The findings show that community-based interventions, led to stunting reduction rates ranging from 15% to 25% in developing countries. This research can serve as a reference for stunting intervention policies through nutrition education, WASH (water sanitation and hygiene), and supplementary food.